Soil chemical attributes after the superficial distribution and without incorporation of limestone doses - Sampaio, Marinez Carpiski; Oliveira, Paulo Sérgio Rabello de; Rego, Carlos Augusto Rocha de Moraes; Mattei, Eloisa; Piano, Jeferson Tiago; Santos, Reginaldo Ferreira (Scientia Agraria Paranaensis, 2022)
Limestone, a common soil amendment in agriculture, is used to correct soil acidity by raising pH, increasing Ca and Mg levels, and neutralizing Al. This study evaluated the effectiveness of surface application of calcitic limestone doses to correct acidity at different soil depths. The research was conducted in a Eutroferric Red Latosol using a randomized block experimental design with eight repetitions in 30 m2 plots, covering a total area of 960 m2. Four doses of calcitic limestone (0, 3, 6, and 9 t ha-1) were applied without mechanical incorporation into the soil. Evaluations were performed at 12 and 24 months after the doses were applied, at depths of 0-0.05, 0.05-0.10, and 0.10-0.20 m, measuring chemical attributes such as pH, H+Al, Al, Ca, Mg, BS, and m. As the calcitic limestone doses increased, there were improvements in pH, approaching neutrality, an increase in Ca content, and an elevation in BS, reducing Al content and potential acidity. This demonstrated the effectiveness of calcitic limestone in increasing BS and reducing m. After 2 years, liming with calcitic limestone provided improvements to the root environment up to a depth of 0.20 m, with increased pH and base saturation, as well as reduced Al and H+Al levels. Furthermore, calcitic limestone doses did not influence soil Mg levels.